Lincoln's God : how faith transformed a president and a nation - Zeitz, Joshua (Viking, an imprint of Penguin Random House LLC, 2023)
"Lincoln's wartime spiritual journey from heretic son and cold skeptic to America's first evangelical Christian president, the role his conversion played in the Civil War, and the way it in turn transformed Protestantism. Abraham Lincoln, unlike most of his political brethren, kept organized Christianity at arm's length. He never joined a church and only sometimes attended Sunday services with his wife. But as he came to appreciate the growing political and military importance of the Christian churches, and when death touched the Lincoln household in an awful, intimate way, the erstwhile skeptic effectively evolved into the nation's first evangelical president. The war, he told Americans, was in some fashion divine retribution for the sin of slavery. This is the story of that transformation and the ways in which religion helped millions of Northerners interpret the carnage and political upheaval of the 1850s and 1860s. Rather than focus on battles and personalities, Joshua Zeitz probes the social impact of the war on Northerners' spiritual worldview and the impact of this religious transformation on the war effort itself. Characters include the famous--Harriet Beecher Stowe, Frederick Douglass, Henry Ward Beecher--and ordinary soldiers and their families whose evolving understanding of mortality and heaven and beliefs about mission motivated them to fight. Long underestimated in accounts of the Civil War, religion--specifically evangelical Christianity--played an instrumental role on the battlefield and home front, and in the corridors of government. More than any president before him-or any president after, until George W. Bush-Lincoln harnessed popular religious enthusiasm to build broad-based support for a political party and a cause. He did so as a master politician and sincere believer, though his belief was characteristically heterodox-and widely misunderstood then, as now. After his death and the end of an unforgiving war, Americans needed to memorialize Lincoln as a Christian martyr. The truth was, of course, considerably more complicated, as this original book explores"--